Fred. Guillaume: Roi de Prusse, Prince de Neuchatel - Louis Léopold, Robert, 1794-1835 (artist):::Creator::::::::::::; Gérard, François, Baron, 1770-1837 (artist):::Contributor:::::::::::: (France)
Miniature portrait engraving of Friedrich Wilhelm III, drawn and engraved by Robert Louis Léopold based on the painting by François Gérard.